Análisis de las usabilidad e impacto comercial de las aplicaciones móviles utilizadas en pandemia en los supermercados de la ciudad de Babahoyo. - Solorzano Lozano, Arianna Del Rocío (2022)
The topic to be addressed in this study was to analyze the usability and commercial impact of mobile applications used during the pandemic in supermarkets in the city of Babahoyo, since technology during the pandemic generated a global social impact on the labor market. The telephones of many supermarkets have contributed during the health emergency. Which has caused a significant increase in these applications to improve the quality of service and customer income as well as change the strategy of buying and selling products and services online where they provide the user with comfort and security to save time and money and reduce prevent the risk of contagion from increasing. During this study it was concluded that mobile applications are now the main part of the product offered, measuring the efficiency and satisfaction of users, the quality of home orders as well as the demand in supermarkets, in this case study the objective is propose the use of mobile applications within the supermarkets of the city of Babahoyo.